Protective effect of Fisetin on the lipopolysaccharide-induced preeclampsia-like rats - Ying Li; Yuanyuan Liu; Jinfeng Chen; Jian Hu (Taylor & Francis Group, 2022)
Objective This article is aimed to investigate the function and underlying action mechanism of Fisetin in LPS-induced PE rats. Methods LPS-induced PE-like rat model was established to explore the effects of Fisetin on PE in vivo. Results Fisetin reduced hypertension, proteinuria, TNF-α, IL-6, IL-1β, MDA, and sFlt-1/PlGF ratio, but elevated the placental, fetal weight, GSH and SOD in PE rats. Moreover, Fisetin suppressed TLR4/NF-κB pathway, as well as promoting Nrf2/HO-1 pathway in placental tissues of PE rats. Conclusions Fisetin exerted protective role and modulated the activation of TLR4/NF-κB and Nrf2/HO-1 pathways in PE-like rat models.